Circadian and circaseptan rhythms in implant-based thoracic impedance. (18th June 2015) - Kirchner, J; Paule, S; Beckendorf, C; Achenbach, S; Arnold, M
Abstract: Thoracic impedance (TI) denotes the electrical resistance that is measured between the right ventricular lead and the can of an implantable cardioverter-defibrillator. It is used in medical diagnostics for fluid load monitoring in heart failure patients. We analysed TI for diurnal and weekly components that go along with the recurrent patterns of daily life. TI was measured in 53 patients over 280 d each with a resolution of 1 h. Information about the patients' professional occupation and typical sleeping rhythm was sought. Periodic signal components were identified in the amplitude spectrum, and their main characteristics were derived by cosinor analysis. The typical daily and weekly pattern were reconstructed by Fourier filtering. The Fourier spectrum indicates a strong circadian and a weaker circaseptan component in TI. The latter is significantly elevated in patients who regularly go to work, on error level . Cosinor analysis states a significant circadian rhythm in all patients ( ), with MESOR 61.8, amplitude 1.9, and acrophase 17.5 h. A significant weekly rhythm is found in 25 patients ( ), with amplitude 0.31 and acrophase typically on Wednesday. Both rhythms typically obtain their maximum during the 'active' phase of the period in daily life, i.e. in the afternoon and on working days, respectively, while the minimum is reached in the 'recreative' phase. Circadian and circaseptan variation are hence prevalent components of TI, which can induce impedance changes of several Ohms and thus be an error source for daily TI measurements.